Varian Mauquf Alaih Am Sebagai Alternatif Dalam Pengembangan Wakaf Produktif - Nurodin Usman (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
Mauquf ' alaih or targets of the Waqf is an important element in studies of law of Waqf. Mauquf ' alaih covering fields of life of mankind, such as religious, educational, health, and social. In a consumerist, wakaf mauquf ' alaih service in fields that have been defined and are not experiencing significant development. Whereas in the endowments ' alaih mauquf productive, more varied and dynamic. It could be, ' alaih mauquf mentioned in the deed of pledge a specific field in the form of endowments but extends in its development so that it covers the areas that are not mentioned. Mauquf ' alaih that has been ditentutan it is called mauquf ' alaih typical mauquf ' alaih unspecified and is the impact of the development of the Waqf called mauquf ' alaih ' am. Keywords: productive, wakaf mauquf ' alaih ' alaih mauquf special General Abstrak Mauquf â€˜alaih atau sasaran wakaf merupakan unsur penting dalam kajian hukum wakaf. Mauquf â€˜alaih meliputi bidang-bidang kehidupan umat manusia, seperti keagamaan, pendidikan, kesehatan, dan sosial. Dalam wakaf konsumtif, mauquf â€˜alaih berupa layanan dalam bidang yang telah ditentukan dan tidak mengalami perkembangan yang signifikan. Sedangkan dalam wakaf produktif, mauquf â€˜alaih lebih bervariasi dan dinamis. Bisa jadi, mauquf â€˜alaih yang disebutkan dalam akta ikrar wakaf berupa bidang tertentu tetapi pada perkembangannya meluas sehingga meliputi bidang-bidang yang tidak disebutkan. Mauquf â€˜alaih yang telah ditentutan itu disebut mauquf â€˜alaih khas dan mauquf â€˜alaih yang tidak ditentukan dan merupakan dampak dari perkembangan wakaf tersebut disebut mauquf â€˜alaih â€˜am. Â Kata kunci: wakaf produktif, mauquf â€˜alaih khusus, mauquf â€˜alaih umum. Â